The Pengaturan Sertifikasi Jaminan Produk Halal Di Indonesia - Mutiara Fajrin Maulidya Mohammad (Fakultas Hukum, Universitas Warmadewa, 2021)
The Law about the Guarantee of Halal Products in Indonesia are crucial, it is normal because Indonesian residents who are Muslim, the state are obliged to guarantee the rights of Muslim consumers. The existence of Law No. 33/ 2014 About JPH, which guides the rights and obligations of business actors with halal products, is expected to provide legal certainty and guarantee for Muslim consumers. Strengthened by the issuance of Government Regulation No.31/ 2019 followed by the issuance of Regulation of the Minister of Religion Number 26/2019 About JPH Administrators. This paper was published to describe the implementing agencies and enforcement of halal certification in Indonesia. The method utilized in this paper is the statutory approach, which is carried out by reviewing all laws that are related to the current legal problem. The result is the existence of PP No.31/2019, it is increasingly clear that the closeness of the halal and haram issues in Indonesia. It shows that there are three institutions urgent they have the authority to carry out halal certification in Indonesia, namely BPJPH, LPH, and MUI. BPJPH has the authority to among others, with the Ministries, the form of cooperation must be in accordance with the duties and functions of each ministry. Meanwhile, the procedure for submitting certification is carried out in six stages, starting from submitting an application, completing inspection, determining the LPH, examining/testing by a halal auditor, determining halalness by MUI and finally get a halal certification. The obligation for halal certification in accordance with UUJPH is enforced from 17 October 2019 to 17 October 2024. The implementation is carried out in stages by taking into account the readiness of business actors, the infrastructure for implementing JPH, considering the type of product as primary needs and being used massively.